2020
DOI: 10.1063/5.0013652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma boundary shape on helical core/long-lived mode in tokamak plasmas

Abstract: Helical distortion of the core part of tokamak plasma, which is called a helical core or a long-lived mode, is investigated by means of three-dimensional magnetohydrodynamic equilibrium calculations. It is found that the magnitude of the helical distortion strongly depends on the shape of the plasma boundary for weakly reversed shear plasmas. The triangularity of the boundary enhances the amplitude of helical distortion. In addition, reversed D-shape plasmas also exhibit a helical core. It is also found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…It is also found that such a shaped tokamak can exhibit another bifurcated equilibrium state due to external kink/peeling modes [18]. In addition, reversed D-shape plasmas are found to exhibit a helical core [17].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…It is also found that such a shaped tokamak can exhibit another bifurcated equilibrium state due to external kink/peeling modes [18]. In addition, reversed D-shape plasmas are found to exhibit a helical core [17].…”
Section: Introductionmentioning
confidence: 88%
“…The inputs for the VMEC code are the profiles of the rotational transform ι(s) = ∑ 6 n=0 l n s n = 1/q(s) and pressure p(s) = p 0 ∑ 5 n=0 p n s n that are obtained by interpolating the output from the MEU-DAS code with the method of least squares, where the normalized toroidal flux is given by the poloidal flux as s = ´ψt 0 q(ψ p )dψ p / ´1 0 q(ψ p )dψ p . We impose a fixed boundary condition that has up-down symmetry, and the boundary shape of the plasma is represented in terms of the ellipticity κ, triangularity δ, and aspect ratio A = 3, as described in [17]. To obtain helical cores in the low q min regime, we need to increase the number of radial grid points from N s = 251 to N s = 3001, as discussed in [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations